SCIENCE. A HISTORICAL-PHILOSOPHICAL APPROACH - Garcia Zarate, Oscar (2011)
This article aims to give an account of the characteristics that define the task ofphilosophy and science from the differences that have been occurring between themthroughout history. Thus, it emphasizes the significance of the birth of experimentalscience in the 17TH century and the important role that philosophy has played in theprogress of such process. It also tackles, concisely, issues concerning the work that thephilosophy of science accomplishes as a discipline oriented, on the one hand, to the explicitation of the methodological assumptions of the activity developing the science,and, on the other hand, the conceptual analysis of its products, the scientific theories.